2007
DOI: 10.1139/l06-132
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the fracture process zone in concrete using scanning electron microscopy and numerical modelling using the nonlocal isotropic damage model

Abstract: This paper deals with two aspects of the characterization of the fracture process zone (FPZ) in quasi-brittle materials such as concrete. An overview is given of the possibility of using a destructive technique, such as the scanning electron microscope, and a numerical model, such as the nonlocal isotropic damage model (NLIDM), to detect FPZ characteristics, e.g., length and width of the FPZ. The fracture of concrete requires the consideration of progressive damage, which is usually modelled by a constitutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Zhang and Wu [3], who indicated that the saturated FPZ moved ahead and shrank as the crack extended; thus, the length of the FPZ decreased after saturation. The maximum length of the fully developed FPZ was approximately 90 mm, which is in excellent agreement with the results of Hadjab et al, who used acoustic emission [6] and scanning electron microscopy [56]. However, the length of the FPZ may be dependent on size and geometry [3] and may also be influenced by aggregate characteristics [15].…”
Section: The Crack Length and Length Of The Fpzsupporting
confidence: 88%
“…Zhang and Wu [3], who indicated that the saturated FPZ moved ahead and shrank as the crack extended; thus, the length of the FPZ decreased after saturation. The maximum length of the fully developed FPZ was approximately 90 mm, which is in excellent agreement with the results of Hadjab et al, who used acoustic emission [6] and scanning electron microscopy [56]. However, the length of the FPZ may be dependent on size and geometry [3] and may also be influenced by aggregate characteristics [15].…”
Section: The Crack Length and Length Of The Fpzsupporting
confidence: 88%
“…Due to the important role of FPZ during fracture process in concrete, it is significant to be able to measure the size of the FPZ and on this basis to investigate the role of the FPZ in the size dependence of fracture parameters. Recently various measurement techniques are already employed to track the fracture process in concrete experimentally, for example the holographic interferometry method [8], the scanning electron microscopy method [9,10], acoustic emission (AE) techniques [11] and digital image correction (DIC) method [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dislocations or microcracks are crystalline defects and are easily detected by an electronics device such as a high resolution microscope [8,9]. These defects can affect the macro crack by amplifying or reducing the stress field around a crak-tip.…”
Section: Dislocationsmentioning
confidence: 99%